2002
DOI: 10.1136/vr.150.6.167
|View full text |Cite
|
Sign up to set email alerts
|

Support needs of veterinary surgeons during the first few years of practice: perceptions of recent graduates and senior partners

Abstract: Postal surveys or personal interviews of 76 recent veterinary graduates and their 49 employers were undertaken to establish their perceptions of good practice when integrating a new graduate into a business and their preferred methods of assessment and development. Practice type and location were the main influences on graduates looking for their first job. Interviews were mostly informal. Employers expected basic veterinary competence and candidates expected good quality support. Most graduates (93 per cent) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 2 publications
5
64
0
1
Order By: Relevance
“…Several surveys of UK graduates (Riggs et al 2001;Routly et al 2002;) provided consistent though lower-quality evidence that dealing with financial aspects of practice, client communication, and managing time and volume of work (prioritising) are significant problems for new graduates in the transition to work.…”
Section: Table 3 Near Herementioning
confidence: 99%
“…Several surveys of UK graduates (Riggs et al 2001;Routly et al 2002;) provided consistent though lower-quality evidence that dealing with financial aspects of practice, client communication, and managing time and volume of work (prioritising) are significant problems for new graduates in the transition to work.…”
Section: Table 3 Near Herementioning
confidence: 99%
“…These programmes are designed to develop the attributes required for graduates to make a rapid transition to independent practice after graduation. Surveys reveal that new graduates experience a varying period of adjustment before practicing effectively as entry level professionals (Heath 1997;Heath and Mills 1999;Riggs et al 2001;Routly et al 2002). This suggests that the quality of graduates' transition to entry level professional autonomy may differ from that intended by veterinary educators.…”
Section: Introductionmentioning
confidence: 93%
“…Although some graduates demonstrate a rapid transition to professional autonomy, others require significant and prolonged support to meet the requirements of their role (Heath and Mills 1999;Riggs et al 2001;Routly et al 2002).…”
Section: Observations Of the Success Of New Graduates' Transition To mentioning
confidence: 98%
“…It is mostly discussed in papers published in the early 2000s but the need to improve client communications remains a key non-technical competency addressed by the literature. In a survey of recent graduates and senior partners Routly et al (2002) found that, in addition to more practical experience, many senior veterinarians listed a greater commitment in undergraduate training to financial/legal skills and communication skills. This sentiment was echoed by the recent graduates surveyed.…”
Section: The Emphasis On Communicationmentioning
confidence: 99%